Conservative-characteristic method for solving hyperbolic systems of equations on triangular computational grids - Goloviznin, Vasily M.; Gorbachev, Daniil Y.; Afanasiev, Nikita A. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2022)
This article considers a conservative-characteristic numerical method for solving hyperbolic systems of equations on triangular computational grids. The main steps of the algorithm are described with the example of solving two-dimensional shallow water equations. The method is verified and compared with the methods developed by other authors on the main tests for shallow water equations over a flat bottom.